SISTEM PENETAPAN DAN PEMUNGUTAN PAJAK SARANG BURUNG WALET DI KABUPATEN MINAHASA UTARA - Pongoh, Meybi Marliane; Ilat, Ventje (Universitas Sam Ratulangi, 2016)
Local tax is an obligatory contribution which is made by the region government for taxable individual or institution without an equal directly rewards, which is used to sponsoring goverment performance and development. Taxation of swift’s nest is a tax on the extraction and exploitation of swift’s nest. This thesis discusses about system of establishment and collection of swift’s nest which aims to determine a fair taxation system accordance with fairness collection tax principle and it’s mechanism undertaken by govermentas know as department of revenue MINUT. The analytical method of this thesis is qualitative descriptive. The result of this research are show that the determination of swift’s nest taxation is already accordance with it’s fairness collection tax principle and it’s already well underway. So that the target of swift’s nest taxation revenue is already realized. Although, there are some constraints in term of collecting swift’s nest taxation at MINUT. Keywords : Swift’s Nest Taxation, Tax’s astablisment, Tax’s Collection.